ANALISIS HUBUNGAN KOMPENSASI DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN ADMIN DI PT DYNAMIC SUCCES GLOBALINDO - Sandi, Dennie Putra; Sihombing, Christina N.; Tobing, Emerald GM (Universitas Kristen Indonesia, 2016)
The research was conducted at PT Dynamic Success Globlindo to determine the relationship of compensation and motivation on employee productivity Admin section. The purpose of this study was to determine the relationship of the compensation and productivity of employees, the relationship between motivation and productivity of employees working at the Admin section PT Dynamic Success Globlindo. This research is descriptive-correlation with population of more than 150 employees, and the data were analyzed using Spearman Rank analysis. The results of this study indicate that (1) there is a significant relationship between compensation and productivity of employees of PT Admin section Dynamic Success Globlindo. It is aimed to obtained t (3.836) is greater than t table (2.002). (2) there is a significant relationship between motivation and productivity of employees of PT Admin section Dynamic Success Globlindo. It is aimed to obtained t (5.753) is greater than t table (2.002). Based on the results, it can be concluded that the thing to be considered again by PT Dynamic Success Globlindo in a compensatory increase was an increase in incentives based on the craft and the presence of a predetermined, overtime / overtime earned in accordance with the number of hours of work that has been determined by the company and bonus received appropriate predetermined targets. Things need to be considered again by PT Dynamic Success Globlindo in increased motivation is to create a conducive working environment to maximize productivity, holding seminars and training which are in accordance with the field work and the additional benefits provided by the company in the form of life and health insurance. Things need to be considered again by PT Dynamic Success Globlindo in increasing the productivity of labor is the increase in the face of various types of characters customer and be able to explain about the condition as well as complaints from customers, an increase give sales targets as an indicator of productivity and increase the potential or skill possessed by reference how many prospects or presentations made. Keywords : compensation, motivation, employee productivity.